2017
DOI: 10.1007/s11011-017-0091-4
|View full text |Cite
|
Sign up to set email alerts
|

Mevastatin promotes neuronal survival against Aβ-induced neurotoxicity through AMPK activation

Abstract: Statins or HMG-CoA reductase inhibitors have been shown to be effective at lowering cholesterol levels, and the application of these molecules has gradually emerged as an attractive therapeutic strategy for neurodegenerative diseases. Epidemiological studies suggest that statin use is associated with a decreased incidence of Alzheimer's disease (AD). Thus, statins may play a beneficial role in reducing amyloid β (Aβ) toxicity, the most relevant pathological feature and pathogenesis of AD. However, the precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Kornelius et al, who evaluated the neuroprotective effects of mevastatin against Aβ deposition-induced neurotoxicity in SK-N-Mc human neuroblastoma cells, reported that this protection was associated with AMPK activation that may increase insulin sensitivity. They demonstrated that mevastatin reduced insulin resistance and Aβ deposition-induced neurotoxicity as a result of AMPK activation [ 67 ]. In another study, Singh et al examined the efficacy of lovastatin and 5-aminoimidazole-4-carboxamide ribonucleotide, an AMPK activator, in experimental autoimmune encephalomyelitis in the murine model of multiple sclerosis, and showed that combination therapy provided more protection for mitochondria/peroxisome and myelin/axons than treatment with either alone.…”
Section: Ampk-associated Therapeutic Effects Of Statinsmentioning
confidence: 99%
“…Kornelius et al, who evaluated the neuroprotective effects of mevastatin against Aβ deposition-induced neurotoxicity in SK-N-Mc human neuroblastoma cells, reported that this protection was associated with AMPK activation that may increase insulin sensitivity. They demonstrated that mevastatin reduced insulin resistance and Aβ deposition-induced neurotoxicity as a result of AMPK activation [ 67 ]. In another study, Singh et al examined the efficacy of lovastatin and 5-aminoimidazole-4-carboxamide ribonucleotide, an AMPK activator, in experimental autoimmune encephalomyelitis in the murine model of multiple sclerosis, and showed that combination therapy provided more protection for mitochondria/peroxisome and myelin/axons than treatment with either alone.…”
Section: Ampk-associated Therapeutic Effects Of Statinsmentioning
confidence: 99%
“…In addition, statins have anti-inflammatory, antioxidant, and neuroprotective effects and are classified into two categories: hydrophilic (fluvastatin, mevastatin, and pravastatin) and lipophilic (simvastatin, lovastatin, atorvastatin) [ 209 ]. In vitro assays have shown that the use of these drugs decreases Aβ levels, and it has been proposed that they activate ADAM10 [ 210 ] and increase the activity of phospholipid transporters (PLTP), which results in the reduction of p-tau181 ( Table 1 ) [ 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 ].…”
Section: Therapymentioning
confidence: 99%
“…Subsequently, Greco et al investigated the effect of AICAR on tau pathology and the downstream mechanism and they found that it reduces the formation of hyperphosphorylated tau by inhibiting GSK-3β [131]. Similarly, using different AMPK activators, Kim et al, Park et al, and Kornelius et al also showed that AMPK activation decreases tau hyperphosphorylation by inhibiting GSK-3β [38,127,133]. In these studies, the antitauopathy effect through GSK-3β inhibition was clearly implicated as the effects were reversed by compound C.…”
Section: Ampk and Tauopathymentioning
confidence: 99%